The Impact of the ESMOD Pattern-making Method on Fashion Design Students in Developing their Knowledge, Technical Skills, and Creative Abilities. (Al-Academy, 2026)
The research investigates the effects on student learning outcomes of the ESMOD pattern-making technique in a Saudi Arabian Fashion and Textile Design Program. The research evaluates the ESMOD method's ability to improve student understanding and practicaldesign abilities when compared to standard ready-made patterns used in numerous educational programs. The research design combined descriptive qualitative methods with experimental quantitative approaches. The research team distributed standardized surveys to both students and teaching staff to obtain their responses. The student participants received instruction through either the ESMOD method or the traditional profile method while following identical learning objectives to maintain equal assessment conditions.The research examined four essential areas which included concept discrimination and process discrimination for cognitive aspects and knowledge application and innovation for skills-based aspects. The Mann-Whitney U test results showed that the ESMOD group outperformed the other group through better median scores and wider performance ranges. The ESMOD method received positive feedback from faculty members through their Likert-scale qualitative survey responses which supported its effectiveness in teaching outcomes. The research demonstrates that the ESMOD method delivers substantial improvements to both theoretical and practical abilities of fashion design students so its adoption should be considered in educational programs of fashiondesign for improved outcomes and achieving learning objectives.